Diskriminantas: Skirtumas tarp puslapio versijų

275 pridėti baitai ,  prieš 9 metus
:Kai <math>x_2=x_3=-\frac{x_1}{2},</math> tai
:<math>x_1^2+x_2^2+x_3^2=x_1^2+\left(-\frac{x_1}{2}\right)^2+\left(-\frac{x_1}{2}\right)^2=x_1^2+\frac{x_1^2}{2}=-2p;</math>
:<math>x_1 x_2+x_1 x_3+x_2 x_3=x_1\cdot\left(-\frac{x_1}{2}\right)+x_1\cdot \left(-\frac{x_1}{2}\right)+\left(-\frac{x_1}{2}\right)\cdot \left(-\frac{x_1}{2}\right)=-x_1^2+\frac{x_1^2}{4}=p;,</math>
:<math>-2(-x_1^2+\frac{x_1^2}{4})=2x_1^2-\frac{x_1^2}{2}=-2p.</math>
:Taip pat ir su ''q'', kai <math>x_2=x_3=-\frac{x_1}{2},</math> tai
:<math>x_1 ^3+x_2 ^3+x_3^3=x_1\cdot ^3+\left(-\frac{x_1}{2}\right)\cdot ^3+\left(-\frac{x_1}{2}\right)^3=x_1^3-2\cdot \frac{x_1^3}{8}=x_1^3-\frac{x_1^3}{4}=\frac{4 x_1^3-x_1^3}{4}=\frac{3 x_1^3}{4}=q3q;</math>
:<math>x_1 x_2 x_3=x_1\cdot \left(-\frac{x_1}{2}\right)\cdot \left(-\frac{x_1}{2}\right)=\frac{x_1^3}{4}=-q,</math>
:<math>(-3)\cdot \frac{x_1^3}{4}=\frac{-3 x_1^3}{4}=(-3)\cdot(-q)=3q.</math>
 
*'''Pavyzdis'''. Išspręsti lygtį
<math>x^3-19 x+30=0.</math>
Anoniminis naudotojas